2021
DOI: 10.1177/1073858421990000
|View full text |Cite
|
Sign up to set email alerts
|

Heart Matters: Cardiac Dysfunction and Other Autonomic Changes in Parkinson’s Disease

Abstract: It has been more than 200 years since James Parkinson made the first descriptions of the disease that bears his name. Since then, knowledge about Parkinson’s disease has been improved, and its pathophysiology, diagnosis, and treatments are well described in the scientific and medical literature. However, there is no way to prevent the disease from its progressive nature yet and only its symptoms can be minimized. It is known that the process of neurodegeneration begins before the onset of motor signs and sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 98 publications
0
18
0
Order By: Relevance
“…Additionally, the evaluation of myocardial function has revealed that, in general, it worsens in PD subjects and specially as the disease progresses [82]. Altogether, these results may be related to the increased prevalence of heart failure in PD [29,79,83] (Figure 2). An open debate exists regarding the origin of abnormalities in the electrocardiographs of PD subjects: some studies point out that they might be caused as a consequence of some parkinsonian treatments, while others have found no relationship [79,80,83].…”
Section: Clinical Manifestationsmentioning
confidence: 93%
See 4 more Smart Citations
“…Additionally, the evaluation of myocardial function has revealed that, in general, it worsens in PD subjects and specially as the disease progresses [82]. Altogether, these results may be related to the increased prevalence of heart failure in PD [29,79,83] (Figure 2). An open debate exists regarding the origin of abnormalities in the electrocardiographs of PD subjects: some studies point out that they might be caused as a consequence of some parkinsonian treatments, while others have found no relationship [79,80,83].…”
Section: Clinical Manifestationsmentioning
confidence: 93%
“…The sympathetic system controls increases in heart rate, while the parasympathetic one is in charge of its decrease [29]. Different evidence points out that in the early phases of PD, there might be a decrease in parasympathetic activity and an increment in sympathetic activity, resulting in the dysregulation of the autonomous system [30].…”
Section: Cardiac Sympathetic Loss In Pdmentioning
confidence: 99%
See 3 more Smart Citations